Pengaruh Penggunaan Media Pembelajaran Augmented Reality (AR) Terhadap Hasil Belajar IPA Siswa Kelas V di SDIT Qurrata Aini Baitussalam - shofiatul mustafidah; Muhammad Fahri; Abrista Devi (Alifbata : Jurnal Pendidikan Dasar, 2025)
This study aims to determine the effect of using Augmented Reality (AR) learning     media on the science learning outcomes of fifth-grade students at SDIT Qurrata Aini         Baitussalam. The method used is an experiment comparing a control class and an             experimental class. The results show that students in the experimental class who           used AR learning media achieved higher test scores compared to students in the             control class. Statistical testing using the Independent Samples T-Test was    conducted to examine the significance of the differences in learning outcomes    between the two classes. Prior to hypothesis testing, the Kolmogorov-Smirnov normality test confirmed that the data were normally distributed, meeting the             assumptions for parametric testing. The test results showed a significant t-value (-    10.123) with a p-value of 0.000 (p < 0.05). The p-value, which is well below the         significance level of 0.05, and the absolute t-value exceeding the t-table value       (approximately 3.623) indicate a significant difference between the average science           learning outcomes in both classes. Therefore, it can be concluded that the use of             Augmented Reality learning media has a positive effect on the science learning        outcomes of students.